ANALISIS PENGARUH RASIO KEUANGAN, BOPO DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA BMT DI DAERAH ISTIMEWA YOGYAKARTA SEBELUM DAN SELAMA PANDEMI COVID-19 - PINKANNIA DIAH TIFFANY; SAHABUDIN SIDIQ (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
This research is motivated by the factors that affect the profitability ratio as a measure of the health level of BMT before and during the pandemic. This study aims to determine the effect of liquidity ratios such as the current ratio (CR), solvency ratios such as DAR and DER, operational efficiency such as BOPO and company size then covid-19 as a dummy variable on the Profitability Ratio (ROA) of BMT in DIY for the period 2016 to 2021. This study uses the static Generalized Method of Moments (GMM) analysis method which can analyze the parameter estimation obtained from the statistical model using panel data. The results of data analysis show that CR, DAR, DER, company size have no significant effect on profitability (ROA), but BOPO and Covid-19 variables show significant results on profitability (ROA).